Book Review: Jens Lehne, Crisis at the WTO: Is the Blocking of Appointments to the WTO Appellate Body by the United States Legally Justified? - Charlotte Sieber-Gasser (sui-generis)
The US policy of blocking new appointments to the WTO Appellate Body relied on a number of legal arguments against the body’s work and ultimately succeeded in rendering the appellate mechanism of the WTO dispute settlement system inoperable in December 2019. In his book, Jens Lehne carefully analyses the various legal arguments officially brought forward by the US until summer 2019. His analysis is proof of the vulnerability of the WTO: despite equality of WTO members enshrined in the WTO treaties, the fate of the WTO remains largely dependent on the willingness of large economies to comply with a legally binding dispute settlement system.